Of mice and Mooshaber - Fuks, Ladislav (Beletrie., 2014)
Ladislav Fuks is an outstanding Czech writer, whose works primarily consist of psychological fiction focusing on the themes of anxiety and life in totalitarian systems. He is well known for his short fiction treating the theme of holocaust, specifically for his works The Cremator (Spalovac mrtvol), which was filmed in 1969, and Mr. Theodore Mundstock (Pan Theodor Mundstock). Natalia Mooshabr's Mice (Myši Natálie Mooshabrové) is his first novel, in which he abandoned the theme of the holocaust moving on to the horror genre. The story takes place in an unspecified country whose ruler was overthr.